Composition, isotopic fingerprint and source attribution of nitrate deposition from rain and fog at a Sub-Arctic Mountain site in Central Sweden (Mt Åreskutan). Issue 1 (1st January 2019) - Vega, Carmen P.; Mårtensson, E. Monica; Wideqvist, Ulla; Kaiser, Jan; Zieger, Paul; StrÖm, Johan
Abstract: While dry and rain deposition of nitrate (NO3 − ) and ammonium (NH4 + ) are regularly assessed, fog deposition is often overlooked. This work assesses summer fog events contribution to nitrogen deposition and availability for forest ecosystems. Rain and fog samples were collected at Mt Åreskutan, Sweden, during CAEsAR (Cloud and Aerosol Characterization Experiment), in 2014. NH4 + + NO3 − represent (31 ± 25) % of total rain ion amount, and (31 ± 42) % in fog. Based on ion concentrations and the nitrate stable isotope signatures δ ( 15 N) and δ ( 18 O), it was possible to detect the plume generated by the Västmanland forest fire; NO x emissions from oil rigs and Kola Peninsula; and the plume of Bardarbunga volcano, Iceland. Scavenging of ions by fog was more efficient than by rain. Rain NH4 + and NO3 − deposition was (26 ± 36) μmol m −2  d −1 and (23 ± 27) μmol m −2  d −1, respectively. Fog NH4 + and NO3 − contributed (77 ± 80) % to total wet deposition of these species. Upscaling rain deposition fluxes to 1 year gave an inorganic nitrogen deposition of (18 ± 16) mmol m −2  a −1 ((252 ± 224) mg m −2  a −1  N equivalents), whereas fog deposition was estimated as (59 ± 47) mmol m −2  a −1 ((826 ± 658) mg m −2  a −1  N equivalents). Annual fog deposition was four times higher than previously reported for the area which only considered rain deposition. However, great uncertainty on the calculation of fog deposition need to be bear in mind. These findings suggest that fog should be considered in deposition estimates of inorganic nitrogen and major ions. If fog deposition is not accounted for, ion wet deposition may be greatly underestimated. Further sampling of wet and dry deposition is important for understanding the influence of nitrogen deposition on forest and vegetation development, as well as soil major ion loads.